Ludus and civilisation : play as an emancipatory concept from the perspective of critical theory - Föhr, Eetu (2021)
This study focuses on the concept of play by examining its emancipatory potential. The dichotomy of work and play forms the crux of the thesis and demonstrating a way to overcome their antagonistic tension is necessary for establishing a conceptual basis for a radically different mode of existence. The framework guiding this examination is offered by the critical theory of the Frankfurt school whose notions define the worldview and methods that are followed. With those ideas laying the groundwork, examining some prominent representatives of game studies develops a more accurate understanding of the concept of play and different ways of approaching it, in addition to tackling some emerging conceptual difficulties. Finally, the study takes an extensive look at psychoanalysis, treating Freudian notions first as a challenge for a world formed around the principles of play and then following Herbert Marcuse to demonstrate how psychoanalytic premises support emancipatory struggles that turn work into play. Hence play receives legitimacy as way of being in a radically different and humane world and as a way of demonstrating the possibility of this kind of existence.